O curso de educação intercultural em debate: um olhar etnomatemático sobre relações comerciais a partir do tema contextual cultura e comércio - Silva, Matheus Moreira da (2022)
Awareness regarding Brazilian social causes and particularly the commercial indigenous relations are becoming widely necessary and ethically required. This awareness results from political and educational concern, among other factors, over the marginalization indigenous peoples are subjected to amid the controversy and dilemmas of cultural diversity in Brazil. In this scenario, there are many actions meant to facilitate the right to protection and improvement of commercial relations of indigenous peoples in distinct contexts. According to this argument, the emancipation of indigenous peoples is becoming a recurrent discussion in academic intercultural courses. Based on the previous statements, the aim of this dissertation, which refers to the dynamics of training indigenous professors, is to determine the way in which the Intercultural Education course from the Federal University of Goiás (UFG) contributes to raising the awareness of undergraduate indigenous students about commercial relations and the logic of capitalism, which interfere daily in the socio-cultural balance of their communities. Theoretically, the discussion will be sustained by D’Ambrosian Ethnomathematics, according to which, throughout history, each population developed its own knowledge and skills. Methodologically, the research was characterized as interpretive, and the analysis of the records will be carried out by the descriptive method. Thus, the study analyzes the contextual theme "Culture and Commerce", of the Intercultural Education course at UFG, from the classes from 2019 to 2021, approaching the indigenous commercial issue from a critical perspective and the influence of capitalism, in order to understand the problems faced by these people.In this degree, the dissertation studies the influences of capitalism in indigenous contexts which modify the traditional commercial relations and indicate some genocide behaviors which occurred, and still continue, as a result of these exploratory actions. With this, this research contributes to the appreciation of the sociocultural reality and traditional commercial relations, through a space that awakens in the students intentions of new searches for critical and conscious action in their reality. Lastly, it may indicate, as well, the influences of the commercial modifications resulted from the interests surrounding society and a possible appreciation for the knowledge and the commercial relations of the indigenous peoples.